Evaluation of the Quality of Clinical Guidelines for Cardiac Rehabilitation. Issue 1 (January 2015) - Serón, Pamela; Lanas, Fernando; Ríos, Eddy; Bonfill, Xavier; Alonso-Coello, Pablo
<x xml:space="preserve">Abstract</x> PURPOSE: To evaluate the quality of clinical guidelines (CGs) for cardiac rehabilitation and to critically appraise exercise-related recommendations. METHODS: Design: critical review. Data sources: main search engines, databases, clearinghouses, and guideline developers. Study selection: We included evidence-based CGs specific to cardiac rehabilitation with recommendations for the period after diagnosis of myocardial infarction or acute coronary syndrome. Clinical guidelines needed to include an exercise component and at least 1 additional component in the cardiac rehabilitation program. Data extraction and appraisal: We evaluated the quality of GCs, using the Appraisal of Guidelines for Research and Evaluation Instrument, second version. Three reviewers independently extracted data, appraised the quality of included CGs, and resolved disagreements by consensus. RESULTS: Nine guidelines were included. The average scores were 79.84%, 59.88%, 55.56%, 85.18%, 48.92%, and 56.79% for the domains of scope and purpose, stakeholder involvement, rigor of development, clarity and presentation, applicability, and editorial independence, respectively. The majority of guidelines recommended low- to moderate-intensity aerobic and resistance exercises, with moderate variability in the frequency and duration of sessions. CONCLUSIONS: Clinical guidelines consistently recommended aerobic and resistance exercises. Overall, our critical review showed that the quality of CGs was at least moderate, with the greatest deficiencies being related to applicability and rigor of development domains.